Angiotensin converting enzyme inhibitors and angiotensin receptor blockers in an outbreak of SARS-CoV-2 - Didar Yanardag Acik (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
In COVID-19, hypertension, diabetes mellitus, coronary artery disease, and immunosuppression are comorbid conditions most often associated with poor prognosis. Angiotensin converting enzyme inhibitors and/or angiotensin receptor blockers are widely used in the treatment of these diseases. Therefore, scientists turned their attention to these drugs and brought up the question of whether angiotensin converting enzyme inhibitors and angiotensin receptor blockers may be drugs that adversely affect prognosis in SARS-CoV-2 infection. The authors generally discussed the role of these drugs in SARS-CoV-2 infection through the same mechanisms. We also investigated the effects of these drugs on the immune system.